(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The period of preschool education is an important stage for the development of children’s creative abilities. During this period, children have the opportunity to express their thoughts, develop their imagination and engage in creative activities. However, there are a number of educational problems in this process that can prevent children from fully developing their creative abilities.